The Influence Of Role Ambiguity On Employee Creativity Through Role Conflict As An Intervening Variable - Suryani, Ni Kadek; Usmany, Paul; Wibowo, Teguh Setiawan; Salabi, Ahmad; Kune, Debiyanti; Sandy Wendikasari, Luh Ade Calista (LPPM Institut Nasional Laa Roiba Bogor, 2024)
Roles that are ambiguous, do not have clear specifications and functions, along with role conflicts that often clash, researchers believe will increase employee creativity because employees must improve from the problems/conflicts they have so that their performance is good, the company's performance is good, and they can be trusted in many tasks / targets that a company has. Therefore, this study aims to analyze the influence of Role Ambiguity on Employee Creativity with Role Conflict as a moderating variable. This research is a quantitative research, with an explanatory approach which researchers obtained from collecting questionnaires from Pegadaian insurance employees spread throughout Indonesia with the criteria of having worked for at least 1 year. This data can also be called primary data. The data was analyzed using the smart PLS 4.0 analysis tool. The results show the Role Ambiguity variable can have a positive relationship and a significant influence on Employee Creativity because the -Values value is positive and is below the 0.05 significance level, namely 0.024. Apart from that show that the Role Conflict variable can moderate the relationship between Role Ambiguity and Employee Creativity because the P-Values value is positive and has a value below the significance level of 0.05, namely 0.000, which is smaller than the direct test of 0.024. In this way, the two research hypotheses above can be accepted and proven comprehensively and scientifically.